Isolation And Identification Of Dominating Viable Bacterial Species In Potable Water - PAVAN KUMAR PINDI,; B. RAVALI,; S. PRASAD,; K. ARCHANA,; D. RAJENDAR,; N.RANGAIAH, (International Journal of Pharma and Bio Sciences, 2012)
This paper aims at the analysis of viable bacteria in potable water. Bacteria are the most diverse living beings on earth and only a fraction of them have been identified. The study aims to analyze bacterial abundance in potable water. Sample collection was carried out in 13 different places of Mahabubnagar district of Andhra Pradesh, India. The species were identified based on morphology, biochemical, antibiotic sensitivity tests and 16S rRNA gene approach. 33 different morphotypes were found in the samples. Among them 4 dominating strains were considered for further studies. The 16S rRNA gene sequences revealed that Bacillus, Enterobacter, Exiguobacterium and Staphylococcus were dominating in these samples. Overall, 16S rRNA gene sequencing and biochemical tests revealed that these bacterial groups are potentially active in potable water.